Hubungan Pola Menstruasi dengan Kejadian Anemia pada Remaja Putri di Wilayah Pesisir Kota Bengkulu: The Relationship of Menstrual Patterns with Anemia in Adolescent Women in Coastal Areas Bengkulu City - Anggun Dineti; Deni Maryani; Yetti Purnama; Asmariyah Asmariyah; Kurnia Dewiani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Anemia is a severe global public health problem, especially in the age range of 15-49 years. Indonesia ranks 5th (22.331%) with the most anemia globally. Anemia can occur in adolescent girls. Adolescent girls have a higher risk of anemia than teenage boys. Anemia happens because young women experience menstruation which causes blood loss every month, so they need twice as much iron during menstruation. An abnormal menstrual pattern is a risk factor for anemia. SMKN 6 Bengkulu City and SMAN 7 Bengkulu City are the 1st and 2nd highest coastal areas with risk factors for anemia in adolescent girls in Bengkulu City. Determine the relationship between menstrual patterns and the incidence of anemia in adolescent girls in the coastal area of Bengkulu City. This research design implemented a cross-sectional approach. The research sample amounted to 60 respondents. Further, the study used an accidental sampling technique. The data analysis employed chi-square. 31 young women (51,67%) experienced abnormal menstrual patterns, 29 people (48, 33%) experienced normal menstrual patterns, 34 people (56.66%) were not anemic, and 26 people (43, 34%) had anemia. The results of the bivariate analysis showed that the p-value = 0.000 < a = 0.05. This study concludes that Ha is accepted, so there is a relationship between menstrual patterns and the incidence of anemia in adolescent girls in the coastal area of Bengkulu City. Young women are expected to increase their knowledge and be willing to take Fe tablets every month.